KUALITAS PELAYANAN BERPENGARUH TERHADAP KEPUASAN PENGUNJUNG PERPUSTAKAAN - Naruliza, Esty; Purwaningsih, Faradillah Sandhy (Fakultas Ekonomi Universitas IBA, 2017)
Library is one of the information providers engaged in the management ofinformation and media services provider education. The library is still a relativelyinexpensive option to meet the needs of visitors. The purpose of this study is todeterminethe effect of service quality on customer satisfaction of service users IBA PalembangUniversity library.Quality of service is any activity carried out by the company in order to meetconsumer expectations. Services in this case is defined as a service or services deliveredby the owner of the service in the form of reliability, responsiveness, assurance, empathyand tangibles in providing services for customer satisfaction. And the satisfaction of acondition that is on the show to consumers after using the service or the service.Sampling method in this research is Stratified Random Sampling but at themoment Accidental questionnaire method. The data used in this research is primary dataobtained from questionnaires distributed to 125 respondents.From the results of multiple linear regression test simultaneously demonstratedservice quality effect on visitor satisfaction with the significance of the library amountedto 599.699 less than 0.05. Partially, 10.30% reliability, responsiveness 18.22%, 14.77%assurance, empathy and tangibles 34.25% 18.46% effect on satisfaction, 96% visitorsatisfaction variation libraries can be explained by the variable quality of service whilethe remaining 4% is explained by other variables not analyzed in this study.Of the five variables, variables Empathy (X4) of 34.25% is the most dominantvariable affecting visitor satisfaction IBA University library service users. This provesthat the library is able to provide library services properly..